Radiofrequency Ablation a Safe and Effective Treatment for Pediatric Benign Nodular Thyroid Goiter - Lin, An-Ni; Lin, Wei-Che; Cheng, Kai-Lun; Luo, Sheng-Dean; Chiang, Pi-Ling; Chen, Wei-Chih; Chen, Yueh-Sheng; Wang, Cheng-Kang; Kan, Na-Ning; Su, Yan-Ye (Frontiers in Pediatrics, 2021)
Purpose: To evaluate the effectiveness of radiofrequency ablation (RFA) for benign thyroid nodules in pediatric patients. Materials and Methods: Twelve pediatric patients (11 female, 1 male; mean age 15.54±2.8 years, range 10–19 years) with benign thyroid nodules (mean longest diameter 4.1±1.4 cm, range 1.5–5.9 cm) treated by RFA from 2017 to 2020 were evaluated. The inclusion criteria for RFA therapy were (i) age <20 years; (ii) benign cytological confirmation by 2 separate ultrasound guided fine-needle aspiration cytology (FNAC) or core needle biopsies; (iii) pressure symptoms or cosmetic problems caused by thyroid nodules; (iv) absence of any sonographic suspicious feature; and (v) follow-up for >6 months. Under local anesthesia, RFA was performed with the use of an RF generator and an 18-gauge internally cooled electrode. Volume changes in nodules on follow-up ultrasonography (US), changes in symptomatic and cosmetic scores, and complications arising during or after RFA were evaluated. Results: Mean follow-up period was 24.9 ± 13.9 months (range 6–43 months). At the last follow-up visits, volume had decreased significantly (15.34±11.52 mL vs 4.07±4.99 mL; P <0.05), whereas volume reduction rate was 74.31%±19.59%. Both cosmetic and compressive symptoms were also significantly improved (2.7±0.9 vs 1.2±1.8 and 1.1±0.7 vs 0.1±0.3; P <0.05). The mean number of ablation sessions was 1.4 ± .6 (range 1–3 sessions), and one of the patients suffered from transient vocal cord palsy which was spontaneously resolved 53 days later. Conclusions: RFA is a safe and effective treatment for benign thyroid nodules in pediatric patients, and can thus serve as an alternative treatment for thyroidectomy.